Validation of an Automated Urea Assay Method Using Bronchoalveolar Lavage Fluid Samples for the Therapeutic Drug Monitoring of Antimicrobials in Severe Pneumonia - Ghaleb, Maeva; Delomez, Julia; Sauzay, Chloé; Durand-Maugard, Charlotte; Bodeau, Sandra; Huriez, Elisabeth; Preudhomme, Maite; Lemaire-Hurtel, Anne-Sophie; Andréjak, Claire; Bennis, Youssef (Therapeutic drug monitoring, 2025)
Determining the concentration of an antimicrobial agent in epithelial lining fluid using therapeutic drug monitoring (TDM) may be clinically useful for optimizing drug exposure in patients with severe pneumonia. The epithelial lining fluid drug concentration can be measured in samples obtained during bronchoscopy and bronchoalveolar lavage (BAL). To account for the dilution induced by the saline instillation procedure, the concentration of the drug in BAL fluid samples is usually corrected using the serum-to-BAL fluid concentration ratio of urea. However, for this analysis to be integrated into daily TDM, a rapid, sensitive, and reproducible urea assay is required. The authors developed and validated a urea assay method for BAL fluid samples using the Atellica Solution automated platform (Siemens Healthcare Diagnostics Inc). They analyzed the urea concentration in BAL fluid and serum samples from 40 patients with severe pneumonia who were included in a prospective cohort study. The results of the automated assay were compared with those obtained using a manual colorimetric assay kit. The automated method was linear between 0.11 and 1.1 mmol/L urea (r 2 = 0.9928, n = 12). The within- and between-day relative errors (accuracy) and coefficients of variation (precision) for the 3 quality controls (0.25, 0.5, and 0.75 mmol/L) were all below 15%. The serum/BAL fluid urea concentration ratio of patients was not significantly different between the automated and manual assays [median (interquartile range): 29.8 (18.5-36.8) versus 26.3 (16.5-41.4), P = 0.2325, respectively], and BAL data of the 2 assays were well correlated (r 2 = 0.8679, slope of the linear regression curve: 1.06 ± 0.07). The turnaround time of the automated method was approximately 30 minutes, which was much faster than that of the manual assay, which required a dedicated technician for almost 3 hours. These results demonstrate the feasibility of an automated urea assay that allows the measurement of drug concentration in the lungs as a routine complementary analysis to the TDM of antimicrobials in severe pneumonia.